Bean Common Mosaic Virus and Bean Common Mosaic Necrosis Virus: Relationships, biology, and prospects for control - Worrall, E.A.; Wamonje, Francis O.; Mukeshimana, G.; Harvey, Jagger J.W.; Carr, J.P.; Mitter, N. (Elsevier, 2015)
The closely related potyviruses Bean common mosaic virus (BCMV) and Bean common mosaic necrosis virus (BCMNV) are major constraints on common bean (Phaseolus vulgaris) production. Crop losses caused by BCMV and BCMNV impact severely not only on commercial scale cultivation of this high-value crop but also on production by smallholder farmers in the developing world, where bean serves as a key source of dietary protein and mineral nutrition. In many parts of the world, progress has been made in combating BCMV through breeding bean varieties possessing the I gene, a dominant gene conferring resistance to most BCMV strains. However, in Africa, and in particular in Central and East Africa, BCMNV is endemic and this presents a serious problem for deployment of the I gene because this virus triggers systemic necrosis (black root disease) in plants possessing this resistance gene. Information on these two important viruses is scattered throughout the literature from 1917 onward, and although reviews on resistance to BCMV and BCMNV exist, there is currently no comprehensive review on the biology and taxonomy of BCMV and BCMNV. In this chapter, we discuss the current state of our knowledge of these two potyviruses including fundamental aspects of classification and phylogeny, molecular biology, host interactions, transmission through seed and by aphid vectors, geographic distribution, as well as current and future prospects for the control of these important viruses.